Respiratory symptoms and lung functional impairments associated with occupational exposure to poultry house pollutants. Issue 3 (3rd July 2021) - Neghab, Masoud; Ebrahimi, Ali; Soleimani, Esmaeel
Abstract : This study aimed to assess respiratory symptoms and the pulmonary function test (PFT) in a group of poultry workers. The prevalence of respiratory symptoms was determined. Airborne concentrations of total and repairable dusts exceeded the threshold limit values. Gram-positive cocci and Cladosporium were the dominant genera of bacteria and fungi, respectively. The prevalence of respiratory symptoms was significantly higher in the exposed subjects. Mean baseline values of forced expiratory volume (FEV1 ), FEV1 to forced vital capacity (FVC) ratio (FEV1 /FVC) and peak expiratory flow (PEF) were significantly lower in the exposed group. Significant cross-shift decrements were noted in vital capacity (VC), FVC, FEV1, PEF and FEV1 /FVC of the exposed subjects. A dominant pattern of lung function abnormality was found to be obstructive. Exposure to poultry pollutants may result in a significant increase in the prevalence of respiratory symptoms as well as both acute reversible and chronic irreversible decrements in the PFT.